2013
DOI: 10.1080/00268976.2013.806683
|View full text |Cite
|
Sign up to set email alerts
|

Distance determination from dysprosium induced relaxation enhancement: a case study on membrane-inserted WALP23 polypeptides

Abstract: Abstract. Membrane incorporated synthetic α-helical polypeptides labeled with Dy(III) chelate complexes and nitroxide radicals were studied by the inversion recovery (IR) technique and Dy(III)-nitroxide distances were obtained. A comparison of obtained distances with the previously reported Gd(III)-nitroxide pulse double electron-electron resonance (DEER or PELDOR) calibration data was performed and revealed reliability of the IR-based technique for the distance determination in membrane-incorporated biomacrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 52 publications
1
21
0
2
Order By: Relevance
“…Such EPR distance measurements rely on the dipole-dipole coupling that is revealed as a broadening in continuous-wave EPR spectra of nitroxide spin labels up to distances of about 20 Å (Rabenstein & Shin, 1995), by relaxation enhancement up to distances of about 30-40 Å ( Jäger, Koch, Maus, Spiess, & Jeschke, 2008;Lueders, Razzaghi, et al, 2013;Voss et al, 2001), and by pulse EPR techniques up to distances of about 80 Å ( Jeschke, 2012;Schiemann & Prisner, 2007). The data obtained by pulse techniques can be converted to distance distributions Jeschke, Koch, Jonas, & Godt, 2002), which is particularly useful in cases where the macromolecule or complex exists in several distinct conformations.…”
Section: Limitations Of Current Techniques To Solve Structures Of Larmentioning
confidence: 99%
“…Such EPR distance measurements rely on the dipole-dipole coupling that is revealed as a broadening in continuous-wave EPR spectra of nitroxide spin labels up to distances of about 20 Å (Rabenstein & Shin, 1995), by relaxation enhancement up to distances of about 30-40 Å ( Jäger, Koch, Maus, Spiess, & Jeschke, 2008;Lueders, Razzaghi, et al, 2013;Voss et al, 2001), and by pulse EPR techniques up to distances of about 80 Å ( Jeschke, 2012;Schiemann & Prisner, 2007). The data obtained by pulse techniques can be converted to distance distributions Jeschke, Koch, Jonas, & Godt, 2002), which is particularly useful in cases where the macromolecule or complex exists in several distinct conformations.…”
Section: Limitations Of Current Techniques To Solve Structures Of Larmentioning
confidence: 99%
“…[37, 38, 39] While several EPR studies were reported, where fast relaxing agents were naturally present in biomacromolecules,[40, 41, 42, 43, 44] the site-directed introduction of EPR relaxation agents and corresponding distance measurements have not yet been examined in detail. This approach is similar to the paramagnetic relaxation enhancement (PRE) approach in NMR, but due to the larger magnetic dipole moment of nitroxide radicals, as compared to any magnetic nuclei, the relaxation enhancement (RE) approach in EPR might access longer interspin distances than PRE.…”
Section: Introductionmentioning
confidence: 99%
“…For smaller monomeric molecules one or more paramagnetic centers can be synthetically built. [36, 39] Specific properties of a certain protein, as, for instance, protection of a labeling site by substrate binding, could be used for orthogonal labeling. [52] An approach that uses unnatural amino acids for nitroxide labeling[53] and a thiol-specific reaction for lanthanide labeling is currently the only tested systematic protocol of orthogonal chemo-selective spin labeling of large monomeric protein molecules.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations